Accumulative response of large offshore steel bridge under severe earthquake and ship impact due to earthquake-induced tsunami flow. (1st March 2017) - Kang, Lan; Magoshi, Kazuya; Ge, Hanbin; Nonaka, Testuya
Highlights: A method used for evaluating damage of bridge under both earthquake and tsunami is presented. Seismic analysis and impact analysis are conducted. Impact force, direction and velocity due to tsunami are obtained based on tsunami analysis. The coupled earthquake-tsunami effect is investigated. The coupled earthquake-tsunami damage cannot be ignored. Abstract: During the 2011 Great East Japan earthquake occurring at the north-east pacific region, serious secondary disasters caused by collision of drifting containers or ships occurred in various structures when tsunami came. Disaster deterioration caused by earthquake and drifting object impact during earthquake and tsunami has become another problem. This study presents an effective method to evaluate the accumulative response of steel bridge under earthquake and large drifting object impact due to tsunami flow, and the earthquake and tsunami come from the same fault motion. The main innovation has to do with the quantification of the earthquake effect and the ship-impact effect due to earthquake-induced tsunami directly into ductility demands, a phenomenon which has not been studied in the past. A series of seismic response analysis and impact analysis are carried out, and damage to the main tower of bridge is evaluated by means of elastic-plastic finite element analysis. This study shows that piers of main tower of bridge can be severely damaged due to the earthquake and ship impact effect compared to only impact effect. An effective evaluated method that could be useful for evaluating damage of lifeline engineering under such mega earthquake and tsunami is proposed.